Effects of Water Quality on Rare Earth Phosphate Mineral Flotation - Jung, Moonchul (Curtin University, 2023)
Owing to freshwater scarcity, the mineral processing industry is transitioning to alternative water sources. Considering the significant influence of water quality on flotation efficiency, a comprehensive understanding of its impact is essential. This PhD study investigated the impact of water quality on the flotation of rare earth phosphate minerals. To understand the fundamental mechanisms, the study employed various techniques, offering critical insights for an industry adapting to different water sources.